An Interview with Matthew Kaiser on Competition and Play - Sean Scanlan (NANO, 2014)
An Interview with Matthew Kaiser on Competition and Play, by Sean Scanlan. Matthew Kaiser, the author of The World in Play: Portraits of a Victorian Concept (Stanford UP, 2012) says that “[c]ompetition is the disease from which modern life suffers,” and that “[c]ompetition is the only cure” for this suffering. This contradictory pairing seems to get at the heart of his thesis: play, as a totalizing, umbrella-like concept, emanates from a host of philosophical, political, and scientific work produced by Victorians who posed many of their ideas of play in sports metaphors, competitive logics, and narratives of struggle. Kaiser goes beyond the dichotomy of competition and play/competition or play, by stating “I’m interested in the totalizing potential of both concepts, the way that play, or competition for that matter, swallows the world whole, becomes in the minds of so many people, the organizing principle of reality, whether of culture or nature or consciousness, or of all three.”